Toward elimination of mother-to-child transmission of HIV in Malawi: Findings from the Malawi Population-based HIV Impact Assessment (2015-2016). - Evelyn Kim; Sasi Jonnalagadda; Juliana Cuervo-Rojas; Andreas Jahn; Danielle Payne; Christine West; Francis Ogollah; Alice Maida; Dumbani Kayira; Rose Nyirenda; Trudy Dobbs; Hetal Patel; et al. (PLoS ONE)
Background Malawi spearheaded the development and implementation of Option B+ for prevention of mother-to-child transmission of HIV (PMTCT), providing life-long ART for all HIV-positive pregnant and breastfeeding women. We used data from the 2015-2016 Malawi Population-based HIV Impact Assessment (MPHIA) to estimate progress toward 90-90-90 targets (90% of those with HIV know their HIV-positive status; of these, 90% are receiving ART; and of these, 90% have viral load suppression [VLS]) for HIV-positive women reporting a live birth in the previous 3 years. Methods MPHIA was a nationally representative household survey; consenting eligible women aged 15-64 years were interviewed on pregnancies and outcomes, including HIV status during their most recent pregnancy, PMTCT uptake, and early infant diagnosis (EID) testing. Descriptive analyses were weighted to account for the complex survey design. Viral load (VL) results were categorized by VLS (<1,000 copies/mL) and undetectable VL (target not detected/below the limit of detection). Results Of the 3,153 women included in our analysis, 371 (10.1%, 95% confidence interval [CI]: 8.8%-11.3%) tested HIV positive in the survey. Most HIV-positive women (84.2%, 95% CI: 79.9%-88.6%) reported knowing their HIV-positive status; of these, 94.9% (95% CI: 91.7%-98.2%) were receiving ART; and of these, 91.2% (95% CI: 87.4%-95.0%) had VLS. Among the 371 HIV-positive women, 76.0% (95% CI: 70.4%-81.7%) had VLS and 66.5% (95% CI: 59.8%-73.2%) had undetectable VL. Among 262 HIV-exposed children, 50.8% (95% CI: 42.8%-58.8%) received EID testing within 2 months of birth, whereas 17.9% (95% CI: 11.9%-23.8%) did not receive EID testing. Of 190 HIV-exposed children with a reported HIV test result, 2.1% (95% CI: 0.0%-4.6%) had positive results. Conclusions MPHIA data demonstrate high PMTCT uptake at a population level. However, our results identify some gaps in VLS in postpartum women and EID testing.